Hydrogenation catalyst, method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202510570111.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
当前,普通氧化铝酸性较为单一、负载金属时与活性组分间的作用太强,导致深度加氢的目的还不能很好的实现
[0081]本发明提供了一种加氢催化剂的制备方法,首先,采用自组装法,主要通过控制醇/铝摩尔比、醇/模板剂摩尔比以及模板剂的引入方式,同时在自组装的过程中引入双功能结构导向剂,结合水热处理,制备比表面积、孔结构和表面酸分布更加适宜的介孔氧化铝;然后,以上述介孔氧化铝材料为基础,将其与具备大孔的高温型活性炭以及部分主活性金属(第VIB族金属)混合成型,得到的加氢催化剂中间体具有更加适宜的孔分布以及B酸酸分布,为后续“内水相/油相/外水相”型多相浸渍液负载提供基础,各步骤综合协调,从而显著提高催化剂脱金属活性性能以及长周期运转性能。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to a hydrogenation catalyst, specifically to a hydrogenation catalyst, its preparation method, and its application. Background Technology
[0002] Heavy oil hydrotreating technology plays an increasingly important role in the efficient utilization and light oil refining of crude oil. Alumina, as the main support for hydrotreating catalysts, possesses characteristics such as a large specific surface area, excellent pore structure, a certain acid strength distribution, and high hydrothermal and thermal stability, thus playing a crucial role in the hydrotreating process. Currently, ordinary alumina exhibits relatively uniform acidity, and the interaction between loaded metals and active components is too strong, hindering the achievement of deep hydrotreating goals. Especially in heavy oil hydrotreating, the small pore size of ordinary alumina restricts the diffusion of large molecules during the reaction, making the catalyst more prone to deactivation, and the utilization rate of active metals needs further improvement.
[0003] CN103539173A discloses a method for preparing a highly thermally stable ordered mesoporous alumina material. This material maintains good pore order after calcination at 1000℃ for 1 hour. It uses inorganic aluminum sources such as aluminum nitrate and aluminum chloride as raw materials, P123 as a template agent, and organic carboxylic acids as surface protectants in ethanol and aqueous solutions. The ordered mesoporous alumina material is synthesized through solvent evaporation-induced self-assembly. The pore size of this material is 4.0–10.0 nm, and the specific surface area is 200–400 m². 2 / g, pore volume 0.3~1.0cm³ 3 / g.
[0004] Currently, there are many ways to synthesize alumina, but how to prepare alumina-based support materials with better overall performance, and on the basis of the above, prepare hydrogenation catalysts with excellent performance, is an important research direction. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a hydrogenation catalyst, its preparation method, and its application. When used in the hydrodemetallization reaction of residual oil, the hydrogenation catalyst of this invention exhibits strong hydrogenation activity, ensuring long-term stable operation of the hydrogenation unit.
[0006] The first aspect of this invention provides a method for preparing a hydrogenation catalyst, comprising the following steps:
[0007] (1) Mix aluminum source, acid and alcohol, and perform pre-hydrolysis to obtain solution A;
[0008] (2) Mix the template agent and alcohol to obtain solution B;
[0009] (3) Mix solution A, solution B and mixture X containing bifunctional structure directing agent and perform hydrothermal treatment. After hydrothermal treatment, drying and calcination, mesoporous alumina is obtained.
[0010] (4) The mesoporous alumina, activated carbon, first active metal source and molding aid obtained in step (3) are mixed and shaped, dried and calcined to obtain a catalyst intermediate;
[0011] (5) Impregnate the catalyst intermediate obtained in step (4) with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, and calcine to obtain the catalyst.
[0012] Further, in step (1), the pre-hydrolysis is carried out under stirring conditions, and the stirring rate is not particularly limited. The temperature of the pre-hydrolysis is 20-60℃, and the pre-hydrolysis time is 1-12 hours. Further, the aluminum source is one or more of aluminum sources such as aluminum nitrate, aluminum chloride, and aluminum isopropoxide. The acid is an inorganic acid, preferably one or more of sulfuric acid, nitric acid, and hydrochloric acid. The alcohol is a low-carbon alcohol, preferably one or more of ethanol, propanol, and butanol.
[0013] Further, in step (1), the alcohol / aluminum molar ratio is 10.0 to 80.0, preferably 10.0 to 60.0.
[0014] Further, in step (1), the acid / aluminum molar ratio is 1.0 to 12.0, preferably 2.0 to 6.0.
[0015] Further, preferably, in step (1), the aluminum source, acid, and alcohol are first mixed and pre-hydrolyzed to obtain a precursor solution, and then an ionic emulsifier is added dropwise to the precursor solution to obtain solution A. The amount of the ionic emulsifier added is related to the amount of the precursor solution by 0–20 g / 100 mL, preferably 5–15 g / 100 mL.
[0016] Furthermore, the ionic emulsifier is one or more of anionic emulsifiers such as sodium dodecyl sulfate and fatty polyoxyethylene ether sulfate salt (chemical structure formula RO(CH2CH2O)n-SO3Na (n=1~15, R is a fatty alkyl group of C10~C22)).
[0017] Further, in step (2), the template agent is at least one of P123 (polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer), SDBS (sodium dodecylbenzenesulfonate) and AOT (dioctyl sulfosuccinic acid), preferably P123.
[0018] Further, the molar ratio of the aluminum source in step (1) to the template agent in step (2) is 50–130, for example, but not limited to 50, 60, 70, 80, 90, 100, 110, 120, 130, etc., and any value within the range formed by any two of these values. Further, after mixing, the mixture is stirred at 20–65°C for 1–6 hours, with no particular limitation on the stirring rate. In step (2), the alcohol is one or more low-carbon organic alcohols such as ethanol, propanol, and butanol. The molar ratio of the alcohol to the template agent is 300–1000.
[0019] Further, in step (3), the mixture X containing the bifunctional structure directing agent includes the bifunctional structure directing agent, an alcohol and an acid, wherein the alcohol is preferably ethanol and the acid is preferably nitric acid; the bifunctional structure directing agent is polyethylene glycol-distearatephosphatidylethanolamine (molecular weight of 500-5000).
[0020] Further, in step (3), the volume ratio of alcohol to acid in the mixture X is 4 to 12. In the mixture X, the ratio of the mass of the bifunctional directed agent to the sum of the volumes of alcohol and acid is 0.05 to 0.85 g / mL, preferably 0.30 to 0.75 g / mL.
[0021] Furthermore, in step (3), the ratio of the molar amount of the bifunctional structure directing agent to the sum of the molar amounts of the bifunctional structure directing agent and the aluminum source in solution A is 0.1 to 0.5.
[0022] Preferably, in step (3), solution A is first added dropwise to solution B to obtain solution C; then, the mixture X containing the bifunctional structure directing agent is added dropwise to solution C for hydrothermal treatment. Further, the conditions for the hydrothermal treatment are: temperature 160-280℃, preferably 180-260℃, time 3-12h, preferably 4-8h.
[0023] Further, in step (3), after the hydrothermal treatment, the alumina is first cooled to room temperature (20-30°C), then dried and calcined to obtain mesoporous alumina. The drying temperature is 120-200°C, and the drying time is 4-10 hours. The calcination temperature is 500-650°C, and the calcination time is 3-8 hours.
[0024] Further, in step (4), the activated carbon is a high-temperature activated carbon, with a minimum heat resistance temperature of not less than 700℃, preferably 750~850℃. The activated carbon has a pore volume of 1.0~1.8mL / g, and the pore volume with a pore size of 50.0~300.0nm accounts for 15%~45% of the total pore volume.
[0025] Further, in step (4), the molding aid is one or more of guar gum powder, methylcellulose, etc. The molding method can be at least one of extrusion, tableting, and ball rolling. The shaped product can be clover-shaped, four-leaf clover-shaped, butterfly-shaped, cylindrical, spherical, or strip-shaped, etc.
[0026] Further, in step (4), the mass of the molding aid added is 1.0% to 8.0% of the total mass of mesoporous alumina and activated carbon.
[0027] Further, in step (4), the first active metal is one or more of VIBs, preferably Mo and / or W; further, the molybdenum source is selected from at least one of ammonium heptamolybdate, ammonium tetramolybdate, molybdenum oxide, etc.; the tungsten source is ammonium metatungstate. The mass (based on oxides) of the first active metal source is 8% to 20% of the total mass of mesoporous alumina and activated carbon.
[0028] Further, in step (4), the drying temperature is 120–200°C, and the drying time is 4–10 h. The calcination temperature is 500–650°C, and the calcination time is 3–8 h.
[0029] Furthermore, in the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, the second active metal includes Group VIB metals and Group VIII metals.
[0030] Furthermore, the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing a second active metal includes an inner aqueous phase, an oil phase coating the inner aqueous phase, and an outer aqueous phase. The inner aqueous phase includes a Group VIB metal, a co-emulsifier, a water-soluble polymer, water, and an optional source of additives. The outer aqueous phase includes a Group VIII metal, a hydrophilic agent, and water. The oil phase includes a surfactant and oil.
[0031] Further, the mass ratio of surfactant to oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0, more preferably 1.0:4.0 to 10.0, for example 1.0:4.0, 1.0:4.5, 1.0:5.0, 1.0:5.5, 1.0:6.0, 1.0:6.5, 1.0:7.0, 1.0:7.5, 1.0:8.0, 1.0:8.5, 1.0:9.0, 1.0:9.5, 1.0:10.0, etc., and any value within the range formed by any two of these values.
[0032] Furthermore, the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0, for example 0.5:1.0, 0.7:1.0, 0.9:1.0, 1.0:1.0, 1.5:1.0, 2.0:1.0, 3.0:1.0, 4.0:1.0, 5.0:1.0, 6.0:1.0, 7.0:1.0, 8.0:1.0, 9.0:1.0, etc., and any value within the range formed by any two of these values.
[0033] Furthermore, the mass ratio of the "internal aqueous phase / oil phase" to the external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.0, for example 0.5:1.0, 0.7:1.0, 0.9:1.0, 1.0:1.0, 1.5:1.0, 2.0:1.0, 3.0:1.0, 4.0:1.0, 5.0:1.0, 6.0:1.0, 7.0:1.0, 8.0:1.0, etc., and any value within the range formed by any two of these values.
[0034] Furthermore, the water-soluble polymer is one or more of polyvinyl alcohol (molecular weight 170,000 to 220,000), carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate (molecular weight less than 10,000).
[0035] Furthermore, in the internal aqueous phase, the mass concentration of the water-soluble polymer is 4.0% to 14.0%.
[0036] Furthermore, in the inner aqueous phase, the concentration of Group VIB metals as oxides is 8-80 g / 100 mL, preferably 10-60 g / 100 mL; in the outer aqueous phase, the concentration of Group VIII metals as oxides is 2-50 g / 100 mL, preferably 5-30 g / 100 mL.
[0037] Furthermore, the Group VIB metal is Mo and / or W, and the Group VIII metal is Ni and / or Co. The Group VIB metal source is one or more of ammonium tetramolybdate, ammonium heptamolybdate, molybdenum oxide, ammonium metatungstate, etc., and the Group VIII metal source is one or more of basic nickel nitrate, cobalt nitrate, etc.
[0038] Furthermore, in the internal aqueous phase, the additive is selected from at least one of phosphorus, silicon, or boron, preferably phosphorus, and the phosphorus source is one or more of phosphoric acid, ammonium hydrogen phosphate, and ammonium dihydrogen phosphate. In the internal aqueous phase, the concentration of the additive, calculated as an oxide, is 0–12.0 g / 100 mL, preferably 0.5–12.0 g / 100 mL.
[0039] Further, the co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol, and glycerin. The mass concentration of the co-emulsifier in the internal aqueous phase is 0.5% to 5.0%.
[0040] Further, the hydrophilic agent is one or more selected from polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide. In the external aqueous phase, the mass concentration of the hydrophilic agent is 5.0% to 15.0%.
[0041] Furthermore, the surfactant is selected from glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol (structure R-(PCC)). x -OH, where R is a straight-chain alkyl group with 12 to 15 carbon atoms, and x is 2 to 11, etc.
[0042] Furthermore, the oil is selected from at least one of silicone oil and vegetable oil, the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil, and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.
[0043] Further, in step (2), the preparation method of the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal includes:
[0044] (a) The surfactant and oil are mixed and heated to obtain the oil phase;
[0045] (b) Mix the co-emulsifier, the Group VIB metal source, water and optional auxiliary source, and heat to obtain a clear solution;
[0046] (c) Add a water-soluble polymer to the clear solution obtained in step (b) to obtain an internal aqueous phase;
[0047] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a) while the oil phase remains liquid during the dropwise addition. Simultaneously, stirring and shearing are performed to homogenize the mixture, resulting in an "aqueous phase / oil phase" emulsion.
[0048] (e) Mixing a Group VIII metal source with water containing a hydrophilic agent to obtain an external aqueous phase;
[0049] (f) The “inner aqueous phase / oil phase” type emulsion obtained in step (d) is added dropwise to the outer aqueous phase obtained in step (e) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0050] Further, in step (a), the surfactant is selected from glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol (structure R-(OCC)). x -OH, where R is a straight-chain alkyl group with 12 to 15 carbon atoms, and x is 2 to 11, etc., or one or more of these. The oil is selected from at least one of silicone oil and vegetable oil, wherein the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methylphenyl silicone oil, and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.
[0051] Furthermore, in step (a), the heating is carried out to a temperature of 45–85°C to make the oil phase appear as a uniform liquid.
[0052] Further, in step (a), the mass ratio of the added surfactant to the mass of the oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0.
[0053] Further, in step (b), the co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol, polyvinyl alcohol, and glycerin.
[0054] Further, in step (b), the amount of the co-emulsifier is 0.5% to 5.0% of the mass of the internal aqueous phase obtained in step (c).
[0055] Further, in step (b), the Group VIB metal is Mo and / or W, and the Group VIB metal source can be one or more of molybdenum oxide, ammonium tetramolybdate, ammonium heptamolybdate, ammonium metatungstate, etc. The additive is selected from at least one of phosphorus, silicon, or boron, preferably phosphorus, and the phosphorus source can be one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, etc.
[0056] Further, in step (b), the water is distilled water or deionized water, and the conductivity of the water should be less than 10.0 mS.
[0057] Further, in step (b), the heating is carried out to a temperature of 90-120°C to ensure that the substances added in step (b) are mixed evenly until a clear solution is obtained.
[0058] Further, in step (c), the concentration of Group VIB metals as oxides in the internal aqueous phase is 8-80 g / 100 mL, preferably 10-60 g / 100 mL, and the concentration of additives as oxides is 0-12.0 g / 100 mL, preferably 0.5-12.0 g / 100 mL.
[0059] Further, in step (c), the water-soluble polymer is one or more of polyvinyl alcohol, carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate.
[0060] Further, in step (d), the mass concentration of the water-soluble polymer in the aqueous phase obtained in step (d) is 4.0% to 14.0%.
[0061] Furthermore, in step (d), the oil phase is kept in a liquid state at a temperature of 45–85°C, and the stirring rate is 400–800 r / min.
[0062] Further, in step (d), the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0.
[0063] Further, in step (d), the stirring-shear homogenization process is carried out at a stirring speed of 10,000 to 18,000 rpm, a shear homogenization time of 3 to 8 min, and a shear homogenization temperature of 50 to 85°C.
[0064] Further, in step (e), the Group VIII metal is Ni and / or Co; the Group VIII metal source is one or more of basic nickel carbonate, cobalt nitrate, etc.
[0065] Further, in step (e), the hydrophilic agent is one or more of polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide.
[0066] Further, in step (e), the water is distilled water or deionized water, and the conductivity of the water should be less than 10.0 mS.
[0067] Further, in step (e), the mass concentration of the hydrophilic agent in the external aqueous phase is 5.0% to 15.0%.
[0068] Further, in step (e), the concentration of Group VIII metals in the external aqueous phase, calculated as oxides, is 2 to 50 g / 100 mL, preferably 5 to 30 g / 100 mL.
[0069] Further, in step (e), the mass ratio of the "internal aqueous phase / oil phase" emulsion to the external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.0.
[0070] Further, in step (5), the impregnation is preferably saturated impregnation. After impregnation, the catalyst is obtained by conventional filtration and washing, drying, and calcination. The drying temperature is 120–200°C, and the drying time is 4–10 h. The calcination temperature is 500–650°C, and the calcination time is 3–8 h.
[0071] A second aspect of the present invention provides a hydrogenation catalyst prepared by any of the methods described in the first aspect.
[0072] Further, the catalyst includes a catalyst intermediate and a second active metal, wherein the catalyst intermediate includes mesoporous alumina, activated carbon, and a first active metal; the catalyst intermediate includes macropores and mesopores, wherein the pore volume of mesopores with a pore size of 6.0–25.0 nm accounts for 10.0%–35.0% of the total pore volume, preferably 20.0%–32.0%, and the pore volume of macropores with a pore size of 50.0–300.0 nm accounts for 40.0%–55.0% of the total pore volume, preferably 41.8%–45.0%.
[0073] Furthermore, the first active metal is selected from one or more group VIB metals, preferably Mo and / or W; the second active metal includes at least one group VIB metal and at least one group VIII metal, wherein the group VIB metal is preferably Mo and / or W, and the group VIII metal is preferably Ni and / or Co.
[0074] Furthermore, the specific surface area of the mesoporous alumina is 300–500 m² / g. 2 / g, preferably 330-360m 2 / g, with a mesopore size of 11.0–25.0 nm, preferably 14.0–16.0 nm, and a pore volume of 1.00–1.50 mL / g, preferably 1.20–1.50 mL / g.
[0075] Furthermore, in the mesoporous alumina, the amount of medium-strong acid accounts for more than 55% of the total acid content, preferably 57% to 65%. The total acid content refers to the sum of the amounts of weak acid, medium-strong acid, and strong acid, and the unit of acid content is mmol / g. In the modified mesoporous alumina, the total acid content is 0.230 to 0.270 mmol / g, preferably 0.230 to 0.250 mmol / g.
[0076] Furthermore, in the catalyst, based on the mass of the catalyst, the content of the first active metal as oxide is 10% to 20%, preferably 10% to 18%, the content of the second active metal as oxide is 1% to 10%, preferably 2% to 8%, and the mass ratio of mesoporous alumina to activated carbon is 1.0 to 6.0, preferably 1.5 to 5.0.
[0077] Furthermore, in the catalyst, the mass ratio of the Group VIB metal in the second active metal (calculated as oxide) to the Group VIB metal in the first active metal (calculated as oxide) is 0.1 to 4.0.
[0078] Further, in the catalyst intermediate, the amount of Brønsted acid accounts for 20.0% to 30.0% of the sum of the amounts of Brønsted acid and Lewis acid, preferably 26.0% to 30.0%. In the hydrogenation catalyst, the amount of Brønsted acid is 19.5 to 30.0 μmol / g, preferably 26.0 to 30.0 μmol / g.
[0079] The third aspect of the present invention provides the application of the above-mentioned catalyst in the hydrodemetallization of residue oil.
[0080] Compared with the prior art, the present invention has the following beneficial effects:
[0081] This invention provides a method for preparing a hydrogenation catalyst. First, a self-assembly method is used, mainly by controlling the alcohol / aluminum molar ratio, the alcohol / template molar ratio, and the introduction method of the template agent. Simultaneously, a bifunctional directing agent is introduced during the self-assembly process, combined with hydrothermal treatment, to prepare mesoporous alumina with more suitable specific surface area, pore structure, and surface acid distribution. Then, based on the above-mentioned mesoporous alumina material, it is mixed with high-temperature activated carbon with macropores and some main active metals (Group VIB metals) to form a hydrogenation catalyst intermediate with more suitable pore distribution and Brønsted acid distribution, providing a foundation for subsequent loading in an "internal aqueous phase / oil phase / external aqueous phase" multiphase impregnation solution. The comprehensive coordination of each step significantly improves the catalyst's demetallization activity and long-term operating performance. Detailed Implementation
[0082] The technical solutions and effects of the present invention will be further illustrated below with reference to the embodiments, but the invention is not limited to the following embodiments.
[0083] In this invention, the specific surface area and pore volume of the samples were characterized using a Micromeritiics ASAP2420 fully automated specific surface area analyzer from Micromeritiics, Inc. (USA). The treated samples were loaded into the fully automated specific surface area analyzer for property testing using a low-temperature nitrogen isothermal adsorption method. The specific surface area of the samples was calculated using the BET method.
[0084] In this invention, the determination of L-acid or Brønsted acid is performed using infrared spectroscopy. The instrument used is a Nicot Fourier Transform Infrared Spectrometer-6700 (USA). The determination method is as follows: The sample to be measured is ground and pressed into a thin sheet with a thickness of approximately 0.1 mm, which is then placed in an infrared cell. The in-situ infrared cell is heated from room temperature to 350 °C over a programmed temperature range of 20 min and held for 120 min, then cooled to 200 °C over a 10 min period. The in-situ cell is then evacuated to a vacuum of 0.01 Pa. The sample is scanned as the background spectrum, and pyridine vapor is used as a probe molecule to scan the sample at 200 °C. The total amount of total acid, Brønsted acid, and L-acid can then be obtained. The units for the amounts of Brønsted acid and L-acid are μmol / g.
[0085] In this invention, the acid content of moderately strong acids was determined using the NH3-TPD method. The instrument used was an Auto-Chem II 2920 chemisorption analyzer from Micron Instruments. Ammonia was used as the adsorption / desorption medium, and helium as the carrier gas. Programmed temperature desorption and chromatographic analysis were employed to obtain the acid content in different desorption temperature ranges. The acid content of weak acids corresponds to an ammonia desorption temperature below 200℃, the acid content of moderately strong acids corresponds to an ammonia desorption temperature of 200℃–400℃, and the acid content of strong acids corresponds to an ammonia desorption temperature above 400℃. The unit of acid content is mmol / g, which represents the amount of ammonia adsorbed per gram of molecular sieve. The sum of the acid content of weak, moderately strong, and strong acids is the total acid content.
[0086] In each example of the present invention, the room temperature is 25°C.
[0087] In various embodiments of the present invention, the molecular weight of the bifunctional structure-directing agent polyethylene glycol-distearatephosphatidylethanolamine is 872.14.
[0088] Example 1
[0089] This example illustrates the preparation of an "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal:
[0090] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:9.0. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is polysorbate. The mass ratio of co-emulsifier:molybdenum source (calculated as molybdenum oxide):phosphorus source (calculated as phosphorus oxide):water-soluble polymer:water is 5:22:12:23:113. The mass ratio of oil phase to internal aqueous phase is 1.0:0.9. The mass ratio of nickel source (calculated as nickel oxide):hydrophilic agent:water is 20:18:298. The mass ratio of "internal aqueous phase / oil phase" type emulsion to external aqueous phase is 0.8:1.0.
[0091] (a) Add the surfactant glyceryl monostearate to the silicone oil, heat to 75°C, and wait for the silicone oil to melt to obtain the oil phase;
[0092] (b) Add the co-emulsifier polyethylene glycol-8000, molybdenum oxide and phosphoric acid to deionized water in sequence. A reflux condenser is used during the reaction. The reaction starts at 28°C. During the reaction, the stirring speed is 700 r / min. When the temperature is raised to 115°C, the temperature is maintained for 5 hours. The stirring speed is kept constant until a clear solution is obtained.
[0093] (c) Add water-soluble polymer polyvinyl alcohol to the clear solution obtained in step (b) to obtain an inner aqueous phase;
[0094] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a). During the addition, the temperature of the oil phase is maintained at 75°C, and the mixture is stirred. The shear homogenization rate is 14000 rpm, the shear homogenization time is 4 min, and the temperature during the shear homogenization process is 70°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.
[0095] (e) Add the hydrophilic agent to the water, and then add nickel nitrate to the water containing the hydrophilic agent to obtain the external aqueous phase;
[0096] (f) The “inner aqueous phase / oil phase” type emulsion obtained in step (d) is added dropwise to the outer aqueous phase obtained in step (f) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0097] Preparation of the hydrogenation catalyst in this example:
[0098] (1) Add 118g of aluminum isopropoxide and 68mL of nitric acid to 345mL of ethanol, stir at room temperature for 4h to perform pre-hydrolysis and obtain a precursor solution; add 42g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0099] (2) Add 66g of template agent P123 to 300mL of ethanol and stir at room temperature for 6h to obtain solution B;
[0100] (3) Solution A was added dropwise to B to obtain solution C; 75g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was prepared with 95mL of ethanol and 15mL of nitric acid to form solution X. Solution X was added dropwise to solution C and stirred for 2h. Then, it was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 240℃ for 5h. After hydrothermal treatment, it was cooled to room temperature to obtain solution D; solution D was placed in an oven at 180℃ and the solvent was automatically evaporated until the sample was dry. Then, it was calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0101] (4) 235g of mesoporous alumina, 116g of high-temperature activated carbon (heat resistance temperature of 850℃, pore volume of 1.6mL / g, and pore size of 50~300nm accounting for 40% of the total pore volume), 5.4g of guar gum powder, 62g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate;
[0102] (5) The catalyst intermediate obtained in step (4) is saturated with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, and then dried at 120°C for 4 hours and calcined at 550°C for 3 hours to obtain the catalyst.
[0103] Example 2
[0104] This example illustrates the preparation of an "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal:
[0105] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the surfactant to silicone oil mass ratio is 1.0:1.1. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is polysorbate. The mass ratio of co-emulsifier:molybdenum source (calculated as molybdenum oxide):phosphorus source (calculated as phosphorus oxide):water-soluble polymer:water is 5:22:14:23:172. The mass ratio of oil phase to internal aqueous phase is 1.0:5.0. The mass ratio of nickel source (calculated as nickel oxide):hydrophilic agent:water is 17:18:229. The mass ratio of "internal aqueous phase / oil phase" type emulsion to external aqueous phase is 0.9:1.0.
[0106] (a) Add the surfactant glyceryl monostearate to the silicone oil, heat to 75°C, and wait for the silicone oil to melt to obtain the oil phase;
[0107] (b) Add the co-emulsifier polyethylene glycol-8000, molybdenum oxide and phosphoric acid to deionized water in sequence. A reflux condenser is used during the reaction. The reaction starts at 28°C. During the reaction, the stirring speed is 700 r / min. When the temperature is raised to 115°C, the temperature is maintained for 5 hours. The stirring speed is kept constant until a clear solution is obtained.
[0108] (c) Add water-soluble polymer polyvinyl alcohol to the clear solution obtained in step (b) to obtain an inner aqueous phase;
[0109] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a). During the addition, the temperature of the oil phase is maintained at 75°C, and the mixture is stirred. The shear homogenization rate is 14000 rpm, the shear homogenization time is 4 min, and the temperature during the shear homogenization process is 70°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.
[0110] (e) Add the hydrophilic agent to the water, and then add nickel nitrate to the water containing the hydrophilic agent to obtain the external aqueous phase;
[0111] (f) The “inner aqueous phase / oil phase” type emulsion obtained in step (d) is added dropwise to the outer aqueous phase obtained in step (f) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0112] In this example of hydrogenation catalyst preparation, steps (1), (2), (3), and (5) are the same as in Example 1, except that:
[0113] In step (4), 235g of mesoporous alumina, 51g of high-temperature activated carbon (heat resistance temperature of 850℃, pore volume of 1.6mL / g, and pore size of 50~300nm accounting for 40% of the total pore volume), 5.4g of guar gum powder, 48g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate.
[0114] Example 3
[0115] The "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal in this example is the same as in Example 1.
[0116] Preparation of the hydrogenation catalyst in this example:
[0117] (1) Add 56g of aluminum isopropoxide and 32mL of nitric acid to 296mL of ethanol, stir at room temperature for 4h to perform pre-hydrolysis and obtain a precursor solution; add 24g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A;
[0118] (2) Add 26g of template agent P123 to 200mL of ethanol and stir at room temperature for 6h to obtain solution B;
[0119] (3) Solution A was added dropwise to B to obtain solution C; 75g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was prepared with 120mL ethanol and 23mL nitric acid to form solution X. Solution X was added dropwise to solution C and stirred for 2h. Then, it was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 210℃ for 4h. After hydrothermal treatment, it was cooled to room temperature to obtain solution D; solution D was placed in an oven at 180℃ and the solvent was automatically evaporated until the sample was dry. Then, it was calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0120] (4) 235g of mesoporous alumina, 116g of high-temperature activated carbon (heat resistance temperature of 850℃, pore volume of 1.6mL / g, and pore size of 50~300nm accounting for 40% of the total pore volume), 5.4g of guar gum powder, 62g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate;
[0121] (5) The catalyst intermediate obtained in step (4) is saturated with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, and then dried at 120°C for 4 hours and calcined at 550°C for 3 hours to obtain the catalyst.
[0122] Example 4
[0123] The "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal in this example is the same as in Example 1.
[0124] In this example, steps (4) and (5) of the preparation process of the hydrogenation catalyst are the same as in Example 1, except that:
[0125] (1) Add 112g of aluminum isopropoxide and 42mL of nitric acid to 325mL of ethanol, stir at room temperature for 4h to perform pre-hydrolysis and obtain a precursor solution; add 42g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0126] (2) Add 62g of template agent P123 to 320mL of ethanol and stir at room temperature for 6h to obtain solution B;
[0127] (3) Solution A was added dropwise to B to obtain solution C; 58g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was taken and mixed with 68mL of ethanol and 10mL of nitric acid to prepare solution X. Solution X was added dropwise to solution C and stirred for 2h. Then, it was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 160℃ for 5h. After hydrothermal treatment, it was cooled to room temperature to obtain solution D; solution D was placed in an oven at 180℃ and the solvent was automatically evaporated until the sample was dry. Then, it was calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0128] Example 5
[0129] The "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal in this example is the same as in Example 1.
[0130] In this example, steps (4) and (5) of the preparation process of the hydrogenation catalyst are the same as in Example 1, except that:
[0131] (1) Add 88g of aluminum isopropoxide and 34mL of nitric acid to 260mL of ethanol, stir at room temperature for 4h to perform pre-hydrolysis and obtain a precursor solution; add 32g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0132] (2) Add 48g of template agent P123 to 260mL of ethanol and stir at room temperature for 6h to obtain solution B;
[0133] (3) Solution A was added dropwise to B to obtain solution C; 54g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was taken and mixed with 140mL ethanol and 25mL nitric acid to prepare solution X. Solution X was added dropwise to solution C and stirred for 2h. Then, it was transferred to a hydrothermal reactor for hydrothermal treatment at 160℃ for 5h. After hydrothermal treatment, it was cooled to room temperature to obtain solution D; solution D was placed in an oven at 180℃ and the solvent was automatically evaporated until the sample was dry. Then, it was calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0134] Comparative Example 1
[0135] In this example, mesoporous alumina was prepared according to the method described in the literature ("Preparation and Properties of Templated Mesoporous Alumina Materials." Journal of Dalian Railway Institute 27.1 (2006): 71-75).
[0136] Weigh 118g of aluminum isopropoxide and dissolve it in 345mL of deionized water. Add 68mL of nitric acid to form a sol. Stir the solution in an 80℃ water bath for 1h. When the solution cools to room temperature, weigh 66g of P123 and dissolve it in the solution. Stir for 1h. Then transfer the solution to a stainless steel autoclave lined with polytetrafluoroethylene for hydrothermal reaction at a filling degree of 70% and a hydrothermal reaction temperature of 100℃ for 24h. After the hydrothermal reaction is completed, let the autoclave cool to room temperature and dry the reaction product in an oven at 60℃. Then calcine it in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0137] The "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal in this example is the same as in Example 1.
[0138] The hydrogenation catalyst in this example was prepared according to the method in Example 1.
[0139] Comparative Example 2
[0140] This example of mesoporous alumina is the same as in Example 1.
[0141] The preparation method of the impregnation solution containing the second active metal in this example includes the following steps:
[0142] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:9.0. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, and the hydrophilic agent is polysorbate. The mass ratio of co-emulsifier:molybdenum source (calculated as molybdenum oxide):phosphorus source (calculated as phosphorus oxide):water is 5:22:12:113. The mass ratio of oil phase to internal aqueous phase is 1:0.9. The mass ratio of nickel source (oxidizing agent):hydrophilic agent:water) is 20:18:298. The mass ratio of "internal aqueous phase / oil phase" emulsion to external aqueous phase is 0.8:1.0.
[0143] (a) Molybdenum oxide and phosphoric acid were added to deionized water in sequence. A reflux condenser was used during the reaction. The reaction started at 28°C. During the reaction, the stirring speed was 700 r / min. When the temperature was raised to 115°C, it was maintained for 5 h. The stirring speed was kept constant until a transparent and clear solution was obtained, thus obtaining the internal aqueous phase.
[0144] (b) Add basic nickel carbonate and a hydrophilic agent to water to obtain an external aqueous phase;
[0145] (c) The surfactant glyceryl monostearate, silicone oil, and co-emulsifier polyethylene glycol-8000 were added to the aqueous phase obtained in step (a) while stirring. The shear homogenization rate was 14,000 rpm, the shear homogenization time was 4 min, and the temperature during the shear homogenization process was 70°C. After the droplets were dispersed into an emulsion, an "aqueous / oil phase" type emulsion was obtained.
[0146] (d) Add the “inner aqueous phase / oil phase” type emulsion obtained in step (c) to the outer aqueous phase obtained in step (b) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0147] The hydrogenation catalyst in this example was prepared according to the method in Example 1.
[0148] Compared with Example 1, the hydrogenation catalyst obtained by impregnating the supported catalyst intermediate with an "inner aqueous phase / oil phase / outer aqueous phase" impregnation solution prepared by the method of Comparative Example 2 could not meet the requirements of long-term operation of the hydrogenation test device, and the relative demetallization rate was only 92.96% after 2000 hours of operation.
[0149] Comparative Example 3
[0150] The preparation of the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal in this example is the same as in Example 1.
[0151] The preparation steps (1)(2)(3)(5) of the hydrogenation catalyst in this example are the same as in Example 1, except that high-temperature activated carbon is not added in step (4):
[0152] (4) 351g of mesoporous alumina, 5.4g of guar gum powder, 62g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate.
[0153] Comparative Example 4
[0154] The preparation steps (1)(2)(3)(4) of the hydrogenation catalyst in this example are the same as those in Example 1. The difference is that the impregnation solution used in step (5) is a conventional Mo-Ni-P impregnation solution, wherein the content of molybdenum, nickel and phosphorus in the impregnation solution is the same as that in the impregnation solution of Example 1.
[0155] (5) Prepare a Mo-Ni-P impregnation solution by taking molybdenum oxide, basic nickel carbonate, phosphoric acid and deionized water, and then saturate the catalyst intermediate obtained in step (4) with it. After drying at 120°C for 4 hours and calcining at 550°C for 3 hours, the catalyst is obtained.
[0156] Comparative Example 5
[0157] The preparation steps (1), (2), and (3) of the hydrogenation catalyst in this example are the same as those in Example 1. The difference is that the active metal molybdenum is not introduced in step (4), and the mass of MoO3 introduced into the catalyst by the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation liquid in step (5) is 100% of the total MoO3 loading in the catalyst.
[0158] (4) 235g of mesoporous alumina, 116g of high-temperature activated carbon (heat resistance temperature of 850℃, pore volume of 1.6mL / g, and pore size of 50~300nm accounting for 40% of the total pore volume), 5.4g of guar gum powder and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate;
[0159] (5) Prepare an impregnation solution of “internal aqueous phase / oil phase / external aqueous phase”, then saturate the catalyst intermediate obtained in step (4), and dry it at 120°C for 4 hours and calcine it at 550°C for 3 hours to obtain the catalyst.
[0160] Table 1. Properties of the mesoporous alumina obtained in each example.
[0161]
[0162] Table 2 shows the composition of the hydrogenation catalysts obtained in each example.
[0163]
[0164]
[0165] Table 3 Properties of the hydrogenation catalyst intermediates obtained in each example
[0166]
[0167] Note: *The percentage (%) of the amount of Brønsted acid to the sum of the amounts of Brønsted acid and L-acid in the obtained catalyst intermediate is represented by A;
[0168] **In the obtained catalyst intermediate, the proportion (%) of mesopores with a pore size of 6.0–25.0 nm to the total pore volume is represented by B; the proportion (%) of macropores with a pore size of 50.0–300.0 nm to the total pore volume is represented by c.
[0169] Evaluation test
[0170] Activity stability tests were conducted on Examples 1-5 and Comparative Examples 1-5 using a 200mL fixed-bed hydrogenation test apparatus. The feedstock was residue oil with a density of 983.8 kg / m³. 3 (20℃), S content 2.75wt%, Ni and V contents 28.2μg / g and 58.7μg / g respectively, CCR content 11.7wt%, the demetallization rate after 2000h of operation in Example 1 was 100%, and all others were relative demetallization rates. Specific experimental conditions are shown in Table 4, and experimental results are shown in Tables 5 and 6.
[0171] Table 4 Test Conditions
[0172]
[0173]
[0174] Table 5. Test results of the hydrogenation demetallization catalysts in each example.
[0175] Example 1 Example 2 Example 3 Example 4 Example 5 Relative demetallization rate, % 100 97.72 97.45 96.21 95.87
[0176] Table 6. Experimental results of hydrogenation demetallization catalysts in each comparative example.
[0177] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Relative demetallization rate, % 92.48 92.96 93.14 92.74 93.06
[0178] The specific embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for preparing a hydrogenation catalyst, comprising the following steps: (1) Mix aluminum source, acid and alcohol, and perform pre-hydrolysis to obtain solution A; (2) Mix the template agent and alcohol to obtain solution B; (3) Mix solution A, solution B and mixture X containing bifunctional structure directing agent and perform hydrothermal treatment. After hydrothermal treatment, drying and calcination, mesoporous alumina is obtained. (4) The mesoporous alumina, activated carbon, first active metal source and molding aid obtained in step (3) are mixed and shaped, dried and calcined to obtain a catalyst intermediate; (5) Impregnate the catalyst intermediate obtained in step (4) with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, and calcine to obtain the catalyst.
2. The preparation method according to claim 1, characterized in that, In step (1), the aluminum source is one or more of aluminum nitrate, aluminum chloride, and aluminum isopropoxide; the acid is an inorganic acid, preferably one or more of sulfuric acid, nitric acid, and hydrochloric acid; and the alcohol is a low-carbon alcohol, preferably one or more of ethanol, propanol, and butanol. And / or, in step (1), the temperature of the pre-hydrolysis is 20-60°C and the time of the pre-hydrolysis is 1-12h; And / or, in step (1), the ethanol / aluminum molar ratio is 10.0 to 80.0, preferably 10.0 to 60.0; And / or, in step (1), the acid / aluminum molar ratio is 1.0 to 12.0, preferably 2.0 to 6.
0.
3. The preparation method according to claim 1, characterized in that, In step (1), the aluminum source, acid and alcohol are first mixed and pre-hydrolyzed to obtain a precursor solution. Then, an ionic emulsifier is added dropwise to the precursor solution to obtain solution A. And / or, the ionic emulsifier is one or more of sodium dodecyl sulfate and fatty polyoxyethylene ether sulfate salt; Preferably, the amount of ionic emulsifier added is related to the amount of precursor solution used in a ratio of 0 to 20 g / 100 mL, and more preferably 5 to 15 g / 100 mL.
4. The preparation method according to claim 1, characterized in that, In step (2), the template agent is at least one of P123, SDBS and AOT, preferably P123; And / or, the molar ratio of aluminum source in step (1) to template agent in step (2) is 50 to 130; And / or, in step (2), the molar ratio of alcohol to template agent is 300 to 1000.
5. The preparation method according to claim 1, characterized in that, In step (3), the mixture X comprises a bifunctional structure directing agent, an alcohol, and an acid, wherein the bifunctional structure directing agent is polyethylene glycol-distearatephosphatidylethanolamine, the alcohol is preferably ethanol, and the acid is preferably nitric acid; And / or, in the mixture X, the mass ratio of the bifunctional directed agent to the sum of the volumes of the alcohol and acid is 0.05–0.85 g / mL, preferably 0.30–0.75 g / mL; and / or, in the mixture X, the volume ratio of the alcohol to the acid is 4–12; And / or, the ratio of the molar amount of the bifunctional structure directing agent to the sum of the molar amounts of the bifunctional structure directing agent and the aluminum source in solution A is 0.1 to 0.5; And / or, in step (3), the conditions for the hydrothermal treatment are: temperature 160-280℃, preferably 180-260℃, time 3-12h, preferably 4-8h; And / or, in step (3), the calcination temperature is 500-650°C and the calcination time is 3-8h.
6. The preparation method according to claim 1, characterized in that, In step (4), the activated carbon is a high-temperature activated carbon with a minimum heat resistance temperature of not less than 700°C, preferably 750-850°C; And / or, the activated carbon has a pore volume of 1.0 to 1.8 mL / g, and the pore volume of pores with a diameter of 50.0 to 300.0 nm accounts for 15% to 45% of the total pore volume.
7. The preparation method according to claim 1, characterized in that, In step (4), the molding aid is one or more of guar gum powder and methylcellulose; Preferably, the molding aid is added at a mass ratio of 1.0% to 8.0% of the total mass of mesoporous alumina and activated carbon.
8. The preparation method according to claim 1, characterized in that, In step (4), the first active metal is one or more of the group VIB metals, preferably Mo and / or W; Preferably, the mass of the first active metal source is 8% to 20% of the total mass of mesoporous alumina and activated carbon, calculated as oxides.
9. The preparation method according to claim 1, characterized in that, In step (4), the drying temperature is 120-200℃ and the drying time is 4-10h; And / or, the calcination temperature is 500–650°C, and the calcination time is 3–8 hours.
10. The preparation method according to claim 1, characterized in that, In the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing a second active metal, the second active metal includes Group VIB metals and Group VIII metals.
11. The preparation method according to claim 1, characterized in that, The "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing a second active metal includes an inner aqueous phase, an oil phase coating the inner aqueous phase, and an outer aqueous phase. The inner aqueous phase includes a Group VIB metal, a co-emulsifier, a water-soluble polymer, water, and an optional source of additives. The outer aqueous phase includes a Group VIII metal, a hydrophilic agent, and water. The oil phase includes a surfactant and oil.
12. The preparation method according to claim 11, characterized in that, The mass ratio of surfactant to oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0; And / or, the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0; And / or, the mass ratio of the "internal aqueous phase / oil phase" to the external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.
0.
13. The preparation method according to claim 11, characterized in that, The co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol, and glycerin; And / or, the water-soluble polymer is one or more of polyvinyl alcohol, carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate; And / or, the Group VIB metal is Mo and / or W, and the Group VIII metal is Ni and / or Co; And / or, the additive is selected from at least one of phosphorus, silicon or boron, preferably phosphorus; And / or, the hydrophilic agent is one or more of polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide; And / or, the surfactant is selected from one or more of glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol; And / or, the oil is selected from at least one of silicone oil and vegetable oil, the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil, and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.
14. The preparation method according to claim 11, characterized in that, In the internal aqueous phase, the mass concentration of water-soluble polymer is 4.0% to 14.0%; And / or, in the internal aqueous phase, the mass concentration of the co-emulsifier is 0.5% to 5.0%; And / or, in the internal aqueous phase, the concentration of the additive, calculated as oxide, is 0-12.0 g / 100 mL, preferably 0.5-12.0 g / 100 mL; And / or, in the internal aqueous phase, the concentration of Group VIB metals as oxides is 8-80 g / 100 mL, preferably 10-60 g / 100 mL; And / or, in the external aqueous phase, the concentration of Group VIII metals as oxides is 2 to 50 g / 100 mL, preferably 5 to 30 g / 100 mL; And / or, in the external aqueous phase, the mass concentration of the hydrophilic agent is 5.0% to 15.0%.
15. The preparation method according to claim 11, characterized in that, In step (2), the preparation method of the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal includes: (a) The surfactant and oil are mixed and heated to obtain the oil phase; (b) Mix the co-emulsifier, the Group VIB metal source, water and optional auxiliary source, and heat to obtain a clear solution; (c) Add a water-soluble polymer to the clear solution obtained in step (b) to obtain an internal aqueous phase; (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a) while the oil phase remains liquid during the dropwise addition. Simultaneously, stirring and shearing are performed to homogenize the mixture, resulting in an "aqueous phase / oil phase" emulsion. (e) Mixing a Group VIII metal source with water containing a hydrophilic agent to obtain an external aqueous phase; (f) The "inner aqueous phase / oil phase" type emulsion obtained in step (d) is added dropwise to the outer aqueous phase obtained in step (e) to obtain an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution.
16. The preparation method according to claim 11, characterized in that, In step (a), the heating temperature is 45–85°C; And / or, in step (b), the heating to a temperature of 90–120°C; And / or, in step (d), the stirring-shear homogenization process is carried out at a stirring speed of 10,000 to 18,000 rpm, a homogenization time of 3 to 8 min, and a homogenization temperature of 50 to 85°C.
17. The hydrogenation catalyst prepared by any one of the methods described in claims 1-16.
18. The hydrogenation catalyst according to claim 17, characterized in that, The catalyst comprises a catalyst intermediate and a second active metal, wherein the catalyst intermediate comprises mesoporous alumina, activated carbon, and a first active metal; the catalyst intermediate comprises macropores and mesopores, wherein the pore volume of mesopores with a pore size of 6.0–25.0 nm accounts for 10.0%–35.0% of the total pore volume, preferably 20.0%–32.0%, and the pore volume of macropores with a pore size of 50.0–300.0 nm accounts for 40.0%–55.0% of the total pore volume, preferably 41.8%–45.0%.
19. The hydrogenation catalyst according to claim 18, characterized in that, The specific surface area of the mesoporous alumina is 300–500 m². 2 / g, preferably 330-360m 2 / g, with a mesopore size of 11.0–25.0 nm, preferably 14.0–16.0 nm, and a pore volume of 1.00–1.50 mL / g, preferably 1.20–1.50 mL / g; And / or, in the mesoporous alumina, the amount of medium-strong acid accounts for more than 55% of the total acid content, preferably 57% to 65%.
20. The hydrogenation catalyst according to claim 18, characterized in that, In the catalyst intermediate, the amount of Brønsted acid accounts for 20.0% to 30.0% of the sum of the amounts of Brønsted acid and Lewis acid, preferably 26.0% to 30.0%.
21. The hydrogenation catalyst according to claim 18, characterized in that, In the catalyst, based on the mass of the catalyst, the content of the first active metal, calculated as oxide, is 10% to 20%, preferably 10% to 18%, and the content of the second active metal, calculated as oxide, is 1% to 10%, preferably 2% to 8%. And / or, in the catalyst, the mass ratio of the Group VIB metal in the second active metal (calculated as oxide) to the Group VIB metal in the first active metal (calculated as oxide) is 0.1 to 4.
0. And / or, the mass ratio of mesoporous alumina to activated carbon is 1.0 to 6.0, preferably 1.5 to 5.
0.
22. The application of the hydrogenation catalyst prepared by any of the methods described in claims 1-16 or any of the hydrogenation catalysts described in claims 17-21 in the hydrodemetallization of residue oil.
Citation Information
Patent Citations
Highly thermostable and ordered mesoporous alumina material and preparation method thereof
CN103539173A
